2017
DOI: 10.1002/jor.23618
|View full text |Cite
|
Sign up to set email alerts
|

Modulating the oxidative environment during mesenchymal stem cells chondrogenesis with serum increases collagen accumulation in agarose culture

Abstract: Chondrogenesis of mesenchymal stem cells (MSCs) is induced in culture conditions that have been associated with oxidative stress, although the extent to which the oxidative environment affects differentiation and extracellular matrix (ECM) accumulation is not known. The objectives of this study were to evaluate the oxidative environment during MSCs chondrogenesis in conventional serum-free medium, and the effect of serum-supplementation on intracellular reactive oxygen species (ROS) and chondrogenesis. Young a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 59 publications
2
21
0
Order By: Relevance
“…Insulin was found to be a critical factor for generating histological evidence of redifferentiation [47]. Similar results have been reported for bone marrow MSCs as withholding insulin or ITS from chondrogenic medium greatly suppressed chondrogenesis [48,49]. As demonstrated for immature bovine chondrocytes, cartilage matrix synthesis by primary chondrocytes can be stimulated by insulin [50].…”
Section: Effect Of Insulin On Redifferentiationsupporting
confidence: 68%
“…Insulin was found to be a critical factor for generating histological evidence of redifferentiation [47]. Similar results have been reported for bone marrow MSCs as withholding insulin or ITS from chondrogenic medium greatly suppressed chondrogenesis [48,49]. As demonstrated for immature bovine chondrocytes, cartilage matrix synthesis by primary chondrocytes can be stimulated by insulin [50].…”
Section: Effect Of Insulin On Redifferentiationsupporting
confidence: 68%
“…17 Recently, we reported that supplementing defined chondrogenic medium containing ITS+ with FBS moderately enhanced collagen accumulation in young adult equine MSC cultures. 19 For middle-aged rat MSCs, the effect of serum was more pronounced as GAG and hydroxyproline accumulation, and cell survival improved over defined medium. With serum-supplementation of middleaged rat cultures, the accumulation of GAG (~2 µg/mg w/w) was approximately similar to young adult equine MSCs that were cultured in the same manner, while hydroxyproline accumulation in rat cultures (~0.18 µg/mg w/w) was approximately 50% of equine cultures.…”
Section: Discussionmentioning
confidence: 94%
“…With serum-supplementation of middleaged rat cultures, the accumulation of GAG (~2 µg/mg w/w) was approximately similar to young adult equine MSCs that were cultured in the same manner, while hydroxyproline accumulation in rat cultures (~0.18 µg/mg w/w) was approximately 50% of equine cultures. 19 While differences in variables such as seeding density, scaffold, or duration of chondrogenic cultures limits the extent to which comparisons to additional studies can be considered, it appears possible that with serum-supplementation the chondrogenic potential of adult rat MSCs may be comparable to MSCs from other species.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations